CURIOUS PEARL MASTERS SOUND : An Augmented Reading Science Experience - Braun, Eric , 1971- (CURIOUS PEARL SCIENCE GIRL, 2018)
"Curious Pearl and her friend Sal decide to form a band and make music for the talent contest. As they experiment with different instruments, Pearl sees an opportunity to teach Sal all about sound. Free bonus video content through the Capstone 4D augmented reality app enhances the science experience."